Conversão de tesauros em ontologias: um estudo exploratório - Joice Rodrigues Teixeira (2013)
The study provides an analysis of the structure and conceptual relations convertibility of thesauri in the construction of ontologies. Had as interrogative, the existence of methodological principles that guide the conversion process and how they can drive and enhance the transition of the structure and conceptual relations of the thesaurus. Above all, the aim was to present, based on the scientific literature, discussions and methodologies relating to the conversion of thesauri in ontologies. Specifically sought to: identify in the literature of the field of information science key features relating to the construction of conceptual relations of thesauri and ontologies, in order to grasp what relationships present in the structure of the thesaurus meet expected structure in an ontology; identify the selected methods in the literature and results found in thesauri conversion experiences in ontologies, in order to understand the use of terminology and semantic relations of the thesaurus in the ontology; and finally, point the validity and potential of conversion on the basis of the analysis and systematization of the bibliographic data raised. The survey was developed through a process of Analysis of methodological Content referenced by Bardin (2011), divided into two stages: Step1-Study of construction standards of Thesauri and Ontologiesbuilding Standards, where if you used as a reference for this methodological course, instruments such as the ANSINISO Standard. Z 39.19-2005, Guidelines for the Construction, Format, and Management of Monolingual Controlled Vocabularies, followed by manual Ontology for the Twenty First Century: An Introduction with Recommendations of high-level BFO ontology (Basic Formal Ontology); Step 2- analysis of publications and experiences concerning the conversion of the thesaurus with the empirical analysis of the conversion experience in four publications in the field of CI in order to identify which methodological procedures normally has been discussed in studies and practical applications. In response to the possibilities and limitations in the conversion of thesauri in ontologies, The results show that, although the typology and structure of relationships are different, the nature of relationships and entities is grounded in a similar way, and pointed out that the process of driving can have as guiding principles the design of the relationships, in the manuals and standards of construction of thesauri and ontologies. It was noted that the proposed methods are at the level of experimentation, are barely fleshed out and lack detail on the steps and actions to ensure and certify the implementation of the concepts without losing the ontological commitment expected in the construction of ontologies. It is hoped that these results can contribute significantly to the area of information science, by introducing the theme for national level and cooperate with studies for the improvement of the practices and methods of construction of ontology.